Perkembangan Akuntansi Syariah - Nur Alfaeni, Vivi; Diana, Nana (SINOMIKA Journal: Publikasi Ilmiah Bidang Ekonomi dan Akuntansi, 2023)
The introduction of sharia accounting which cannot be separated from the progress of Islam and the need for non-cash business records is discussed in this note. Al-Baqarah: 282 developed the habit of recording among the community and inspired Muslims to pay attention to registration, which became one of the factors that encouraged cooperation at that time. The term "daily" was used for financial memo books in the era of the Islamic caliphate because accounting had been practiced in Islamic lands for a long time. The word double head by Luca Pacioli is also similar. In this way, we can confirm that the Islamic accounting system was first published when the Quran was revealed at 610 Meters, 800 years before Luca Pacioli published his book in 1494. Islamic accounting is accounting that uses contracts to conduct financial business. compatible with the Koran. - Quran, Hadith and Ijma. Islamic business establishments use financial reporting and business records, which later evolves into Islamic accounting. Accounting has long been understood as a tool to hold business owners accountable, but Islamic accounting is much more than that it also holds business owners and God accountable.